Efektivitas Pemungutan Pajak Hotel Dan Restoran Di Kabupaten Manokwari Provinsi Papua Barat - Johanes Paulus Koromath (JFRES Journal of Fiscal and Regional Economy Studies, 2019)
This study aims to determine the effectiveness of tax collection rate hotels and restaurants and their contribution to Local Revenue in Manokwari Regency in the period of 2014 – 2018. Methods of data collection in this study is the observation non-participant. The variable in this study is the ratio of the effectiveness and contribution to the Local Revenue. Data analysis in this study is quantitative analysis. According to data analysis, the average effective tax collection hotel and restaurants in the Manokwari Regency years 2014 – 2018 amounted to 91 percent, which is categorized effective, while the average contribution of tax revenue hotels and restaurants in the same period is 10,82 percent, which is grouped in a less good category.